El Derecho de adaptación de jornada para la conciliación de la vida laboral y familiar, y su redacción en el RDL 6\2019 - Sánchez-Girón Martínez, Beatriz (2021)
In order to accomplish the effective sex equality between woman and man within the working context, the Royal Legislative Decree 6/2019 has extended the legislation of the rights included in the Spanish Workers’ Statute. One of them, which is the main topic of this paper, is the legal protection, art. 34.8, related to the right to adapt the duration and distribution of their working day. The aim is to achieve the balance between the work duties and family responsibilities, without any reduction of the working time and, therefore, the salary. Nonetheless, the workers are not the owners of this right completely, because in any case it is contingent upon the productive system and organizational characteristics of the company. Taking into account that the almost all of the latter do not include these terms, the RLD provides the worker with a series of guarantees to make effective work and family reconciliation. In effect, the employer must not only justify his refusal, but also propose an alternative schedule as if possible.